Exploring the impact of Investors in People: A focus on training and development, job satisfaction and awareness of the Standard. Issue 3 (1st April 2014) - M. Smith, Simon; Stokes, Peter; F. Wilson, John
Abstract : Purpose: – Investors in People (IiP) is a UK government-backed scheme aimed at enabling organizations to develop their training and development cultures and, thereby, their competitiveness. The purpose of this paper is to examine the perceptions and understandings of individuals in six organizations undergoing IiP to explore recent claims within the literature concerning the Standard's impact on training and development, and job satisfaction. Design/methodology/approach: – Data from 35 semi-structured interviews among managers and employees of six diverse organizations were gathered and analysed. Findings: – The paper identifies three key findings in response to recent literature: first, the findings do not support a causal relationship between IiP and training and development; second, the findings do not support a causal relationship between IiP and job satisfaction; third, and to support the other findings, the results indicate little employee awareness of IiP. Practical implications: – If IiP – UKCES are to realize the potential of their Standard, it needs to find a way to ensure it has a direct and positive impact on skill development. Originality/value: – While much of the previous research has identified associations between IiP and various outcomes, this paper seeks to identify the extent to which these associations can be considered to be causal.